Breeding Prawn Corporation / Lediah Maun ... [et al.] - Maun, Lediah; Mudin, Fazidah; Pg. Mohd, Siti Nor Rabiahtul Adawiyah; Baglah, Mahrinah; Mohd. Jali, Rozeiamy (2009)
As we all know, there are various types of agriculture in Malaysia. We choose the breeding prawn or hatchery of tiger prawn as our business. The main reason we choose this business because there are insufficient numbers of supplier for tiger prawn fry in Sabah. This paper work highlighting the unique of the tiger prawn or its scientific name is Panaeus Monodon. Compare to the other types of prawn, the tiger prawn is the most famous seafood that admirer by the people whose like to eat seafood. Moreover, the agriculture in Malaysia also increases and it will contribute the economic growth. The project also helps the tiger prawn cultivator in Sabah get a sufficient baby prawn to livestock for the purpose operating their business. In this project we provide the delivery service for our customer so that it easier for them to make order. This project will commence on the 1st January 2010, this will be the first private breeding prawn in Sabah located near small village name Kampung Numbak Menggatal. If this project approved by the government, the people in the Kampung Numbak will get benefits from this project. They may improve their standard of living. The infrastructure such as road can be improved for the use of the local community.